Pengembangan Bahan Ajar Keterampilan Membaca Model Graves Mahasiswa BIPA - Dian Uswatun Hasanah; Dwi Kurniasih; Novita Nurul Halimah (Badan Pengembangan dan Pembinaan Bahasa, 2021)
This study aims to develop BIPA teaching materials on reading skills with Graves model. This study uses qualitative research methods that are adapted to conditions in the field. The stages of the Graves model implemented are four stages, namely: 1) needs analysis, 2) determining general and specific objectives, 3) sorting and selecting teaching materials and activities developed, and 4) organizing the content and activities of teaching materials. The results showed that the preparation of teaching materials for reading BIPA UIN Raden Mas Said Surakarta has its own characteristics. This specialty is found in the theme used in teaching materials, namely